Survival of Oak Tasar Silkworm Antheraea proylei J. in Relationship with Age of Leaves in Quercus semecarpifolia and Q. Serrata - Goel, R. K.; Pandey, R. K. (Indian Forester, 1990)
Analysis of condensed tannins content in Quercus serrata and Q. semecarpifolia shows a 3.5 fold and 1.5 fold increase over a period of 45 days of leaf-growth respectively, In Q. semecarpifolia, where there is almost constant level of condensed tannins, preponement of silkworm rearing is not requind but the synchronisation of brushing with leaf sprouting is emphasized for getting maximum sunival of A. proylei J. worms, whereas in Q serrata, early brushing of larvae is quite essential in the light of increased level of condensed tannins from 0.45 per cent to 1.55 per cent within 45-47 days of leaf sprouting.